2019
DOI: 10.3390/joitmc5040098
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Innovation and Firm Performance of Manufacturing Firms in Southeast Asian Emerging Markets: Empirical Evidence from Indonesia, Malaysia, and Vietnam

Abstract: This study aims to investigate the effects of product and process innovations on manufacturing firm performance in Southeast Asian emerging markets. To this end, using a cross-national sample of 2324 manufacturing firms from the World Bank Enterprise Survey (WBES) dataset of 2015, we test the effects of product and process innovations on the sales growth of manufacturing firms in Vietnam, Malaysia, and Indonesia. This study finds that product innovation is positively related to sales growth while new operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 71 publications
(112 reference statements)
3
23
1
2
Order By: Relevance
“…This requires a high commitment from the employees and managers of the companies, which leads them towards competitive improvement and a more sustainable performance. Our findings are similar to those of the studies by Liu and Yoo [81], which report that intangible resources and strategic direction play a determining role in the innovative performance and financial performance of SMEs. In addition, Caballero-Morales [84] reveals that SMEs in the time of the COVID-19 pandemic were more creative and managed to develop new forms of marketing and improve and adapt products to the needs of consumers, all of which allowed them to remain in the market and obtain acceptable economic results to stabilize their operations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This requires a high commitment from the employees and managers of the companies, which leads them towards competitive improvement and a more sustainable performance. Our findings are similar to those of the studies by Liu and Yoo [81], which report that intangible resources and strategic direction play a determining role in the innovative performance and financial performance of SMEs. In addition, Caballero-Morales [84] reveals that SMEs in the time of the COVID-19 pandemic were more creative and managed to develop new forms of marketing and improve and adapt products to the needs of consumers, all of which allowed them to remain in the market and obtain acceptable economic results to stabilize their operations.…”
Section: Discussionsupporting
confidence: 91%
“…This is particularly true in emerging markets as companies are limited in obtaining other resources for strong growth [79,80]. Innovation is considered an effective means of keeping a company competitive, even when the company faces a management crisis [81]. However, the management of innovation processes in the business can be a problem faced by company managers due to the absence of a unified model of innovation-management processes in the company [28].…”
Section: The Management Of Innovation and Its Effects On The Economy ...mentioning
confidence: 99%
“…The 19th paper analyzes the efficiency of zinc-refining companies, which is related to entrepreneurship leading culture for open innovation dynamics, in addition to the triple helix and the efficiency of east Asian zinc smelters [137][138][139].…”
Section: Organizational Entrepreneurship Leading Culture For Open Innovation Dynamicsmentioning
confidence: 99%
“…Examples of technological innovation include the introduction of new products and devices, the introduction of new production methods, and creating new forms of the organizational process. Most of the previous studies have shown a positive relationship between innovation and employment, especially product and process innovation [19][20][21][22]. However, the relationship between innovation and employment is explained from many perspectives.…”
Section: Employment Change and Innovationmentioning
confidence: 99%